Translocation (1;22) in a child with bilateral oblique facial clefts. Issue 6 (June 1988) - Dasouki, M; Barr, M; Erickson, R P; Cox, B
Abstract : An eight month old girl was born with symmetrical bilateral oblique facial clefts and calcaneovarus foot deformity. CT scan of the head showed severe bilateral ocular hypoplasia and normal brain parenchyma. Peripheral blood karyotype showed a de novo balanced translocation between a chromosome 1 and 22. A submicroscopic imbalance secondary to this translocation cannot be ruled out. The pattern of the observed anomalies will help distinguish between oblique facial clefts and amniotic band disruption. Chromosomal studies should be performed in children with such rare malformations.